Dukhūl (Al) ala al-Fi’li - Ali Burhan (ALSINATUNA, 2015)
Many linguists agree that (أل) belongs to important articles in Arabic language. ألis usually used in isim (noun), but sometimes it also can be used in fi’il (act). This condition usually can be found in some poems. This study aims to describe the position of أل in fi’il (act). The conclusion of this article is that أل can be used in fi’il butonly in fi’il mudhari’. However, it belongs to rarely used words in Arabic language, so that it cannot be used as formal standard in supporting theory of language.